Peningkatan Hasil Belajar dan Keterampilan Berpikir Kritis dalam Mengidentifikasi Bentuk Datar Menggunakan Model Problem Based Learning di Kelas 1 SDN Purwantoro 1 Kota Malang (Jurnal Simki Pedagogia, 2023)
Based on observations made in Class I-A SDN Purwantoro 1 Malang, learning mathematics has its weaknesses. The lecturer uses the lecture method to give a flat awakening material. In pre-campaign results, only 15 of her 28 students scored above the lowest score. This research aims to describe the application of problem-based learning models to improve mathematics learning outcomes. In his research he employs two cycles. Each cycle consists of four phases: plan, do, observe, and reflect. Data collection was by observation, interviews, field notes, testing, and documentation. Research results using problem-based learning models to learn the mathematics of plane geometry are making good progress. In cycle 1, the teacher activity score was 93.54% in the very good category, in cycle 2 there was a 100% increase in the very good category, in cycle 1 the student activity score was 83.15% in the "good" category, and cycle 2 increased by 93%. fall into the very good category. From the results of this study, it can be concluded that applying a problem-based learning model can improve the learning outcomes of students in the mathematics subject Recognition of Plane Shapes in Class I of SDN Purwantoro 1 Malang.